Movie Review "The Rainmaker (1997)" Produced by American Zoetrop Constellations Films - Fadhillah, Mutia Siti (Semarang State University Undergraduate Law and Society Review, 2022)
The Rainmaker is a 1997 American legal drama film based on John Grisham's 1995 novel of the same name, and written and directed by Francis Ford Coppola. It stars Matt Damon, Danny DeVito, Danny Glover, Claire Danes, Jon Voight, Roy Scheider,Mickey Rourke, Virginia Madsen, Mary Kay Place and Teresa Wright in her final film role. Differences from the novel. The film follows the book in most details, but changes the order of events: in the book, the confrontation ending with Rudy's self-defense killing of Kelly's abusive husband occurs after the end of the trial, not during. Also, the film leaves out an important piece of information from the book that was a central point of Rudy's case: the fact that the leukemia victim had an identical twin, which would have made a transplant virtually certain to work as it would have been a perfect genetic match.